Small-molecule inhibitors prevent the genotoxic and protumoural effects induced by colibactin-producing bacteria. Issue 2 (14th January 2015) - Cougnoux, Antony; Delmas, Julien; Gibold, Lucie; Faïs, Tiphanie; Romagnoli, Chiara; Robin, Frederic; Cuevas-Ramos, Gabriel; Oswald, Eric; Darfeuille-Michaud, Arlette; Prati, Fabio; Dalmasso, Guillaume; Bonnet, Richard
Abstract : Objective: Colorectal cancers (CRCs) are frequently colonised by colibactin toxin-producing Escherichia coli bacteria that induce DNA damage in host cells and exhibit protumoural activities. Our objective was to identify small molecules inhibiting the toxic effects induced by these colibactin-producing bacteria. Design: A structural approach was adopted for the identification of a putative ligand for the ClbP enzyme involved in the synthesis of colibactin. Intestinal epithelial cells and a CRC mouse model were used to assess the activity of the selected compounds in vitro and in vivo. Results: Docking experiments identified two boron-based compounds with computed ligand efficiency values (−0.8 and −0.9 kcal/mol/atom) consistent with data expected for medicinal chemistry leads. The crystalline structure of ClbP in complex with the compounds confirmed that the compounds were binding to the active site of ClbP. The two compounds (2 mM) suppressed the genotoxic activity of colibactin-producing E coli both in vitro and in vivo. The mean degree of suppression of DNA damage for the most efficient compound was 98±2% (95% CI). This compound also prevented cell proliferation and colibactin-producing E coli -induced tumourigenesis in mice. In a CRC murine model colonised by colibactin-producing E coli, the number of tumours decreased by 3.5-fold in animals receiving the compound in drinking water (p<0.01). Conclusions: These results demonstrate that targeting colibactin production controls the genotoxic and protumoural effects induced by this toxin.